DMF/NaOH/H2O: a metal-free system for efficient and chemoselective reduction of α-ketoamides. Issue 20 (11th September 2019) - Ye, Rongcong; Hao, Feiyue; Liu, Guyue; Zuo, Qingsong; Deng, Lijun; Jin, Zhengneng; Wu, Jiashou
Abstract : A metal-free method for efficient and chemoselective reduction of α-ketoamides using DMF/NaOH/H2 O system has been developed. Abstract : We have developed a transition metal free method for efficient and chemoselective reduction of CO bonds using DMF as a hydrogen source and solvent. α-Ketoamides bearing various functional groups are smoothly reduced to α-hydroxyamides in high yields with the present DMF/NaOH/H2 O reduction system.